Intestinal dysfunction in Parkinson's disease: Lessons learned from translational studies and experimental models. Issue 12 (9th September 2016) - Pellegrini, C.; Colucci, R.; Antonioli, L.; Barocelli, E.; Ballabeni, V.; Bernardini, N.; Blandizzi, C.; de Jonge, W. J.; Fornai, M.
Abstract: Background: Symptoms of digestive dysfunction in patients with Parkinson's disease (PD) occur at all stages of the disease, often preceding the onset of central motor symptoms. On the basis of these PD‐preceding symptoms it has been proposed that PD could initiate in the gut, and that the presence of alpha‐synuclein aggregates, or Lewy bodies in the enteric nervous system might represent one of the earliest signs of the disease. Following this hypothesis, much research has been focused on the digestive tract to unravel the mechanisms underlying the onset and progression of PD, with particular attention to the role of alterations in enteric neurotransmission in the pathophysiology of intestinal motility disturbances. There is also evidence suggesting that the development of central nigrostriatal neurodegeneration is associated with the occurrence of gut inflammation, characterized by increments of tissue pro‐inflammatory markers and oxidative stress, which might support conditions of bowel neuromotor abnormalities. Purpose: The present review intends to provide an integrated and critical appraisal of the available knowledge on the alterations of enteric neuromuscular pathways regulating gut motor activity both in humans and preclinical models of PD. Moreover, we will discuss the possible involvement of neuro‐immune mechanisms in the pathophysiology of aberrant gastrointestinal gut transit and neuromuscular activity in the small and large bowel. Abstract : Patients with Parkinson's disease display intestinal motor alterations, such as infrequent bowel movements and constipation. Both preclinical and clinical studies indicate the occurrence of intestinal dysbiosis, tissue inflammation, and changes in bowel neuromuscular activity. Intestinal motor abnormalities are associated with changes in the neurochemical coding of myenteric neurons, both in the small and large bowel.